Low-Intensity Wheelchair Training in Inactive People with Long-Term Spinal Cord Injury: A Randomized Controlled Trial on Propulsion Technique. (November 2015) - van der Scheer, Jan W.; de Groot, Sonja; Vegter, Riemer J.K.; Hartog, Johanneke; Tepper, Marga; Slootman, Hans; Veeger, DirkJan H.E.J.; van der Woude, Lucas H.V.
ABSTRACT: Objective: The objective of this study was to investigate the effects of a low-intensity wheelchair training on propulsion technique in inactive people with long-term spinal cord injury. Design: Participants in this multicenter nonblinded randomized controlled trial were inactive manual wheelchair users with spinal cord injury for at least 10 yrs ( N = 29), allocated to exercise ( n = 14) or no exercise. The 16-wk training consisted of wheelchair treadmill propulsion at 30%–40% heart rate reserve or equivalent in rate of perceived exertion, twice a week, 30 mins per session. Propulsion technique was assessed at baseline as well as after 8, 16, and 42 wks during two submaximal treadmill-exercise blocks using a measurement wheel attached to a participant's own wheelchair. Changes over time between the groups were analyzed using Mann-Whitney U tests on difference scores ( P < 0.05/3). Results: Data of 16 participants could be analyzed (exercise: n = 8). Significant differences between the exercise and control groups were only found in peak force after 8 wks (respective medians, −20 N vs. 1 N; P = 0.01; r u = 0.78). Conclusions: Significant training effects on propulsion technique were not found in this group. Perhaps, substantial effects require a higher intensity or frequency. Investigating whether more effective and feasible interventions exist might help reduce the population's risk of upper-body joint damage during daily wheelchair propulsion.